Effects of interfacial adhesion on thermal and mechanical properties - Brocks, T. [UNESP] (2012)
Carbon fiber/epoxy matrix composites produced by resin transfer molding (RTM) were investigated in order to define the influence of interfacial adhesion on mechanical and thermal properties. The adhesion was studied through DMA, DSC and TGA thermal analyses and tensile test. SEM analyses of fibers surface and tensile fractures support the conclusion that the composite with higher degradation temperature and Tg value has better interface boundary. Besides, the DMA results corroborate with the same conclusion.